Efficient use of water and nutrients in irrigated cropping systems in the Alqueva region - Tomaz, Alexandra (2018)
In the region of Alentejo, Southern Portugal, as a consequence of the implementation of the Alqueva global irrigation system, agriculture intensification is challenging the sustainability of the farming systems. The demand for water and for fertilizers is increasing but so is the demand for water use efficiency (WUE) and for nutrient use efficiency (NUE). Increasing resource-use efficiency while reducing yield gaps can be addressed by suitable agricultural management practices, as in the case of crop rotations. Based on a demonstration project carried out in two farms located in Baixo Alentejo, within the Alqueva irrigation network, soil fertility parameters, WUE and NUE (for nitrogen, phosphorus and potassium) were studied in three maize-based cropping systems: a maize monoculture (M-M) and two rotations, barley+maize-barley (BM-B) and sunflower-barley+maize (S-BM). The total soil organic matter content increased in the two rotations, an important observation especially in soils with low organic content. The final balance of extractable phosphorus and potassium was positive in the BM-B rotation. Water use efficiency values point to a less balanced performance of the S-BM rotation. The WUE and the nitrogen NUE in the different crops and rotations followed a similar pattern. The M-M and BM-B crop successions showed the best indicators of NUE for nitrogen and phosphorus. In all the cropping systems, the potassium NUE was low, suggesting the need to carefully equate the additions of this nutrient by fertilization.